Dental Implant Placement in Focal Osteoporotic Bone Marrow Defect: a Case Report and Treatment Recommendations - Gintaras Juodzbalys (Stilus Optimus, 2022)
Background: Focal osteoporotic bone marrow defect is asymptomatic radiolucent area usually discovered incidentally during radiographic examination of the jaws. This bone condition can lead to clinical complications during dental implant placement or during osseointegration process. Methods: A 54-year-old woman was referred to private dental implant centre for a dental implant rehabilitation treatment in May 17, 2016. Oral examination revealed a healthy mucosa with no visible pathology. Adentia of tooth #46 and moderate atrophy of the edentulous alveolar process were found. Panoramic radiography of the jaws showed 2 cm x 2 cm radiolucency with irregular borders located in tooth #46 region. The margins of the bone defect were uneven, single trabeculae were visible, and the cortical layer was not deformed. In the absence of signs of pathology, it was decided to perform a dental implant surgery in the edentulous jaw segment #46. Results: The osteoporotic focus was filled with natural bovine bone substitute Cerabone®. The granules were gently condensed to the sides - to the buccal and lingual walls until they filled the entire cavity. A 10 mm long, 4.1 mm diameter Straumann® Tissue Level implant was surgically placed with the shoulder of the implant resting on the margins of the osteotomy. It was proposed six steps protocol for surgical dental implant installation in focal osteoporotic bone marrow defect in mandible. Conclusions: A six-step protocol for surgical placement of dental implants in focal osteoporotic bone marrow defects may be a useful tool for clinicians in implant dentistry.